Electrical properties and thermal stability of Cu-P containing electrically conductive adhesives - Li-Ngee, Ho; Hiroshi, Nishikawa; Tadashi, Takemoto (Universiti Malaysia Perlis, 2010)
Organized by School of Materials Engineering & Sustainable Engineering Research Cluster, 1st - 2nd December 2009 at Putra Brasmana Hotel, Kuala Perlis, Perlis.